Biological control of Hydrilla verticillata Vahl by utilization of the grass carp (Ctenopharyngodon idella Vía). - Rojas, Manuel (2016)
Hydrilla verticillata has become an important aquatic weed of irrigation canals at some rice farms of Guanacaste, Costa Rica. This species slows water flow, often causing flooding in adjacent roads, its control increases overall production costs. To evaluate efficiency of the grass carp in controlling Hydrilla three trials were conducted, with varying densities of the fish. In the preliminary trial, 987 kg/ha of grass carp reduced Hydrilla biomass in nearly 62 m3 in 21 days. During the second trial, treatments with 1264 and 2042 kg/ha of the fish completely eliminated the weed after 30 days. However, during the third trial, 1000 kg/ha of the carp only reduced Hydrilla volume in 19 m3, after 66 days. The ratio kg of carp/initial volume of Hydrilla proved to be more important than just the kg/ha of the carp. It was observed that when such ratio was lower than 0.02, the carp did not provide a satisfactory control of Hydrilla; on the other hand, a ratio higher than 0.05 significantly reduced the weed's biomass. The equilibrium point between weed regrowth and biomass consumed by the carp occurred at a ratio close to 0.03.